2019
DOI: 10.1002/cssc.201901120
|View full text |Cite
|
Sign up to set email alerts
|

Porous Palladium Nanomeshes with Enhanced Electrochemical CO2‐into‐Syngas Conversion over a Wider Applied Potential

Abstract: Electrochemical conversion of CO2 into syngas, which can be used directly in the classical petroleum industrial processes, provides a powerful approach for achieving the recycling of anthropogenic carbon. Pd has previously been reported to be capable of converting CO2 into syngas with various CO/H2 ratios, but only at limited applied potential, which is mainly attributed to fewer active sites exposed toward electrocatalysis. Herein, high‐performance Pd nanomeshes (NMs) assembled with branch‐like Pd nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Cheng et al used quantum mechanics to study the space confinement effect on the performance of Ag and Au NPs for ECC to CO. 54 Pd nanomeshes assembled with branchlike Pd NPs for ECC to CO. 56 The electrochemical conversion from CO 2 to tunable syngas can be realized within a range of applied potential from −0.5 to −0.9 V vs RHE. This was attributed to open channels as well as exposed edge and/or corner active sites, which accelerate charge transmission and facilitate CO 2 adsorption, CO 2…”
Section: Nanoscale Metals For Eccmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al used quantum mechanics to study the space confinement effect on the performance of Ag and Au NPs for ECC to CO. 54 Pd nanomeshes assembled with branchlike Pd NPs for ECC to CO. 56 The electrochemical conversion from CO 2 to tunable syngas can be realized within a range of applied potential from −0.5 to −0.9 V vs RHE. This was attributed to open channels as well as exposed edge and/or corner active sites, which accelerate charge transmission and facilitate CO 2 adsorption, CO 2…”
Section: Nanoscale Metals For Eccmentioning
confidence: 99%
“…Sargent et al found that NPs with high-index facets could suppress CO poisoning and simultaneously promote formic acid synthesis . Pd NPs with abundant high-index surfaces exhibit FE of 97%, and a current density of 22 mA cm –2 at an overpotential of −0.2 V. Fu et al synthesized Pd nanomeshes assembled with branchlike Pd NPs for ECC to CO . The electrochemical conversion from CO 2 to tunable syngas can be realized within a range of applied potential from −0.5 to −0.9 V vs RHE.…”
Section: Nanoscale Metals For Eccmentioning
confidence: 99%
“…As a result, it is imperative to develop remarkable electrocatalysts which significantly speed up the reaction rate and regulate the reaction selectivity toward the target products [16,17]. To date, different types of metal-based electrocatalysts such as Au [18][19][20][21][22][23], Cu [24][25][26][27][28][29][30][31][32][33][34][35][36], Pd [37][38][39][40][41][42][43][44][45][46], Ag [47][48][49][50][51][52][53][54], Bi [32,[55][56][57][58], Sn [59][60][61][62][63] and Co [64]...…”
Section: Introductionmentioning
confidence: 99%